EFFECTIVENESS OF BUSINESS TRANSFORMATION STRATEGY TO INCREASING COMPANY'S INCOME IN PRODUCTS DOOH (DIGITAL OUT OF HOME) IN PT. METRA DIGITAL MEDIA - Yitno Utomo; Rusdiyantoro (UNIPA PRESS, 2019)
This reseach to study the effectiveness of business transformation strategy in PT Metra Digital Media and to know the difference increasing of company earnings in DOOH (Digital Out Of Home) product in PT Metra Digital Media, before and after implementation of business transformation strategy. The sample cases in this research are 22 customer companies that have not followed the business transformation process, which is advertised through the directory and control samples, and 22 customer companies that have been following the business transformation process are advertising through DOOH (Digital Out Of Home). Calculation data analysis using SPSS (Statistical Data Analysis) test that Independent-Samples T-Test. The results showed that the effectiveness of the implementation of business transformation strategy applies to product indicator, payment method, service and sales, because the OR (Odd Ratio) value is higher in companies that choose DOOH, while those that are not effectively selected are indicator of the period of exposure and popularity, the difference increasing of company earnings on DOOH (Digital Out Of Home) products at PT Metra Digital Media before and after the implementation of business transformation strategy is evidenced from p = 0,016 (sig <0,05) and hypothesis is accepted.